Les dynamiques territoriales associées au soja et les changements fonctionnels en Amazonie. Le cas de la région de Santarém, Pará, Brésil - Rubén Valbuena (Confins)
The progressive increase in the international demand for cereals and leguminous plants for human and animal consumption has motivated a continuous expansion in the cultivated land in Brazil. This expansion is encouraged by the interest of multinationals of the agro-alimental sector that have made large investments in the country, and by the aid provided by the government to promote and reassert the agro-exporters activities. This progression has gone as far as the cerrado latitudes and, most recently, in the Amazonia, where it has generated profound transformations in the organization of the area and given new roles to different places. Santarém, a historical city in the Amazon which utilizes its privileged location where the Tapajós and Amazonas Rivers confluence, as well as the northern vertex of the BR-163 highway, is the source of such recent changes. It is an urban center that is leading the process of regional change, which is marked by the conversion and productive specialization in the rural areas.